The Design of Population Data Application Using Unified Modeling Language - Hardiansyah, Alim; Laday, Ravie Kurnia; Suhaeli, Muhammad (Department of Informatics, UIN Sunan Gunung Djati Bandung, 2018)
Population data collection at the sub-district level still uses a manual system. It is causing less efficient time. In this study the application of population data is generated in the sub-district, using web applications and using the Unified Modeling Language design. With the above considerations, we need a system that can solve population data problems. With this application, it is expected that it will facilitate the processing of population data. This new application can accelerate the process of population registration with the help of human resources who can run it. Advice needed human resources that can run the application properly.